Betibeglogene Autotemcel; A new hope for transfusion dependent beta-thalassaemia - Wally, Hiba Tariq; Zulfi, Muhammad Hassan; Jilani, Elahi Sana (Journal of the Pakistan Medical Association, 2023)
Respected Editor, Beta thalassaemia is an autosomal recessive disorder that leads to abnormal production of functional adult haemoglobin because of either inadequate or absent production of the B globin chain (beta+/beta0).1 Transfusion-dependent thalassemia (TDT) is a rare and most severe form requiring life-long blood transfusions. To mitigate the effects of TDT, life-long blood transfusions every 2-5 weeks are required, which can elicit transfusion-based reactions and lead to an iron overload state, which can further cause widespread organ damage despite the use of iron chelation therapy.2 Continue...